Varieties of the letter and autistic objects - Laurent, Éric (Facultad de Psicología (Universidad Nacional de La Plata, Argentina), 2021)
In order to respond to the variety of subjects within the autistic spectrum and the diversity of settings that receive them and pay attention to the language bath in which these subjects are immersed, our work aims at defining the position of a partenaire therapist who respects the multiple aspects that the transforming effect of a new encounter with language can take. From this perspective, rather than searching for an ideal method for the approach of the autistic subject, we present a diversity of results obtained in varied contexts whose constant feature is to sustain the effort of inscribing the subject in all the dimensions of language, the instance of the letter and the treatment of objects outside the body –such as the gaze and the voice–, in a great variety of situations and workshops, while maintaining the learning process (fragment of the manuscript).